Bibliometric And Predictive Analysis On Parental Satisfaction Toward Faith Based Schools - Rahmatika, Nuniek; Suparman; Prasetyo, Puguh Wahyu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
This study aims to explore the development of research related to parental satisfaction with faith-based schools and to build a predictive model for future interest trends using bibliometric and supervised learning approaches. The bibliometric analysis was conducted using the VOSviewer software on 402 articles indexed in Scopus, focusing on co-authorship, keyword co-occurrence, and publication trends from 2010 to 2023. In parallel, a survey was conducted among parents (n=120) to assess key predictors of satisfaction using a supervised classification model. The bibliometric findings indicate that research on faith-based education has grown steadily, with clusters of themes emphasizing parental engagement, religious values, and school choice. The predictive model shows that parental satisfaction is significantly influenced by perceived moral development, academic quality, and alignment with family beliefs. The supervised algorithm achieved an accuracy of 86%, confirming the reliability of the predictive variables. This dual approach offers novel insights into the intellectual landscape of faith-based schooling and practical tools for anticipating parental preferences. The findings have implications for educational institutions and policymakers in designing responsive strategies to maintain trust and competitiveness in faith-based education.